2011
DOI: 10.1186/1475-2859-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation of Escherichia coli and its phoB and phoR genes knockout mutants under phosphate and nitrogen limitations as well as at acidic condition

Abstract: BackgroundThe phosphorus compounds serve as major building blocks of many biomolecules, and have important roles in signal transduction. The phosphate is involved in many biochemical reactions by the transfer of phosphoryl groups. All living cells sophisticatedly regulate the phosphate uptake, and survive even under phosphate-limiting condition, and thus phosphate metabolism is closely related to the diverse metabolism including energy and central carbon metabolism. In particular, phosphorylation may play impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 57 publications
3
53
0
Order By: Relevance
“…Both operons have been shown to be induced under phosphate starvation conditions, with the former being regulated by a promoter located upstream of the pstS gene and the latter regulated by RpoS, PhoB, and CRP (16,17). It has also been shown that regulation under phosphate limitation and regulation under acidic conditions are interconnected through RpoS (18). Thus, it is in-…”
Section: Resultsmentioning
confidence: 99%
“…Both operons have been shown to be induced under phosphate starvation conditions, with the former being regulated by a promoter located upstream of the pstS gene and the latter regulated by RpoS, PhoB, and CRP (16,17). It has also been shown that regulation under phosphate limitation and regulation under acidic conditions are interconnected through RpoS (18). Thus, it is in-…”
Section: Resultsmentioning
confidence: 99%
“…Nishioka et al (2001) achieved 66% PHB with the same strain of microalga grown with CO2 but using a medium that was phosphate-free. The limitation of phosphate changes the balance of ATP and NADPH production during photosynthesis, which is potentially responsible for the metabolic changes in the synthesis of PHB (Marzan and Shimizu, 2011). Under nitrogen limitation, cells no longer produce protein, and there is an accumulation of ATP.…”
Section: Characterization Of the Microalgal Biomassmentioning
confidence: 99%
“…The proteomic analysis results (Supplementary Figure S2) suggest that unstressed Bs has evolved a survival strategy inside stones based on the following: (i) heavy investment in protein synthesis and in preventing their aggregation (ribosomal proteins and GroEL); (ii) detection and response to the changes of the environmental external nutrients (UDP glucose, phosphate and so on) concentrations (LysM, UshA and PhoU) (Buist et al, 2008;Marzan and Shimizu, 2011); (iii) scavenging ROS (superoxide dismutase); and (iv) transport of oxygen (hemerythrin). The presence of enzymes using anaerobic terminal electron acceptors in Bs, Mm and Go (Supplementary Table 7) indicates that formate (HCO 2 − ) and nitrate (NO 3 − ) anaerobic respiration may be possible.…”
Section: First-line Defense Strategiesmentioning
confidence: 99%